Diâmetro folicular e taxa de prenhez em protocolo de sincronização com GnRH ou Benzoato de Estradiol no dia 0 em vacas de corte - Silveira, Ana Paula da; Martins, Mariana de Castro; Gabriel Filho, Luís Roberto Almeida [UNESP]; Castilho, Caliê (My University, 2011)
This work aimed to evaluate the pregnancy rate and follicular diameter using EB or GnRH on the insertion of progesterone implant (D0) in lactating beef cows. Two groups were tested in two experiments. In Exp. 1 were used 61 Nelore cows divided into two groups: G-BE (n = 32) and G-GnRH (n = 29), on D0 was inserted P4 implant (CIDR ) and applied 2 mL of BE (G-BE) or 2.5 mL GnRH (G-GnRH). In D9 was performed ultrasonography (U.S.) to measure the diameter of the dominant follicle (DF) present in the ovary and the implant was removed, with concomitant administration of 2.5 mL of PGF2a and estradiol cypionate (ECP ) followed by calves removal. After 48 hours all the cows were inseminated and the calves returned. In Exp. 2 50 cows were used following the same protocol described above, but the pregnancy was assessed without performing ovarian US. There was no difference (p>0.05) in pregnancy rate between treatments, BE (55%) or GnRH (41%), but the follicular diameter was significantly higher (p<0.05) in pregnant cows treated with EB (10.7 mm vs. 8.5 mm) and in cows treated with GnRH there was no difference (p>0.05) between pregnant and no pregnant cows (11.6 mm vs. 10.2 mm). We concluded the use of GnRH on D0 did not improve the pregnancy rate in lactating beef cows and follicular diameter was greater (p <0.05) in pregnant cows compared to non-pregnant only in G-BE.

Neste trabalho objetivou-se avaliar a taxa de prenhez e o diâmetro folicular utilizando benzoato de estradiol (BE) ou hormônio liberador de gonadotrofinas (GnRH) no dia da colocação do implante de progesterona (D0) em vacas de corte em lactação. Dois grupos foram testados em 2 experimentos. No Exp. 1 foram utilizadas 61 vacas da raça Nelore divididas em 2 grupos: G-BE (n=32) e G-GnRH (n=29). No D0 foi colocado implante de P4 (CIDR® ) e aplicados 2 mL de BE (G-BE) ou 2,5 mL de GnRH (G-GnRH). No D9 foi realizada ultrassonografia (US) para medir o diâmetro do folículo dominante (FD) presente no ovário e retirado o implante, concomitante à administração de 2,5 mL de PGF2α e 0,25 mL de cipionato de estradiol (E.C.P.® ) seguida de remoção dos bezerros. Após 48 horas todas as vacas foram inseminadas e os bezerros retornaram às mães. No Exp. 2 foram utilizadas 50 vacas seguindo o mesmo protocolo descrito acima, porém foi avaliada a prenhez sem realização de US ovariana. Não houve diferença (p>0,05) na taxa de prenhez entre os tratamentos, BE (55%) ou GnRH (41%), mas o diâmetro folicular foi significativamente maior (p<0,05) nas vacas prenhes tratadas com BE (10,7 mm vs 8,5 mm) e nas vacas tratadas com GnRH não houve diferença (p>0,05) entre as prenhes e não prenhes (11,6 mm vs 10,2 mm). Concluí-se que o uso de GnRH no D0 não melhora a taxa de prenhez em vacas no pó-parto e o diâmetro folicular foi maior (p<0,05) nas vacas prenhes quando comparado as não prenhes apenas no G-BE.
Follicle diameter and pregnancy rate in synchronization protocols with gnrh or estradiol benzoate on day 0 in beef cows
Keywords: FTAI; Post-partum; Progesterone; Zebu cattle; IATF; Pós-parto; Progesterona; Vacas zebuínas